Regulator-Cited Cooperation Credit and Firm Value: Evidence from Enforcement Actions - Files, Rebecca; Martin, Gerald S.; Rasmussen, Stephanie J. (The Accounting Review, 2019)
ABSTRACT Regulators claim to reward firm cooperation in the enforcement process. However, critics question which actions constitute firm cooperation and contend that cooperation leads to “harsh” and “unfair” outcomes. Examining 1,162 enforcement actions for financial misrepresentation initiated by the Securities and Exchange Commission and Department of Justice, we find that regulator-cited cooperation credit is best explained by remedial actions and self-reported law violations. Cooperation credit is negatively associated with firm monetary penalties assessed by regulators. Our estimates suggest that firms with cooperation credit realize an average penalty reduction of $23.8 million (49 percent). We also estimate that average reputation-related losses are $756 million (70 percent) lower for firms with cooperation credit. We find no association between cooperation credit and related private action outcomes. Our results provide important insight into what constitutes meaningful cooperation with regulators, and suggest that the benefits can be substantial for firms deemed to be cooperative. JEL Classifications: G38; K22; K42; M41.